Pengaruh Perbandingan Tepung Singkong (Manihot esculenta Cranz) Dan Puree Wortel (Daucus carota L) Terhadap Karakteristik Kue Stik - Askara Diputra, I Made; Timur Ina, Putu; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
This research aims to identify the effect of cassava flour and puree of carrot ratio on the characteristic of stick cake and to find out the ratio of cassava flour and puree of carrot to produce stick cake with the best characteristics. This research used a completely randomized design with the treatment ratio of cassava flour and puree of carrot consisted of three levels such as 90% : 10%, 80% : 20%, and 70% : 30%. The treatment was repeated 3 times so that it is obtained 15 experimental units. The parameters observed were water content, ash content, crude fiber content, beta carotene content and the sensory characteristics (color, texture, aroma, taste and overall acceptability) using hedonic tests. The data were analyzed by analysis of variance and the treatment had a significant effect, followed by the Duncan Multiple Range Test. The results showed that the ratio of cassava flour and puree of carrot had a significant effect on the water content, the ash content, the crude fiber content, beta carotene content but did not significantly affect the sensory characteristics. Ratio of 70% cassava flour and 30% puree of carrot had the best characteristics that were water content of 1.96%, ash content of 2.01%, crude fiber content of 2.29%, beta carotene content of 6.77 mg/100g, color, texture, aroma, taste, and overall acceptance was liked.